Immunomodulation—a general review of the current state-of-the-art and new therapeutic strategies for targeting the immune system - Strzelec, Martyna; Detka, Jan; Mieszczak, Patrycja; Sobocińska, Małgorzata Katarzyna; Majka, Marcin (Frontiers in Immunology, 2023)
Recent years brought tremendous development of biotechnological, pharmacological and medical techniques which can be implemented in functional modulation of the immune system components. Immunomodulation attracts much attention because it offers direct applications in both basic research and clinical therapies. Modulation of non-adequate, amplified immune response enables to attenuate clinical course of the disease and restore homeostasis. Potential targets to modulate immunity are as multiple as components of immune system, thus creating various possibilities of intervention. Although, immunomodulation face new challenges to design safer and more efficacious therapeutic compounds. This review offers a cross-sectional picture of heretofore used and the newest pharmacological interventions, genomic editing and tools from the regenerative medicine range in immunomodulation. We reviewed currently available experimental and clinical evidence to prove efficiency, safety and feasibility of immunomodulation in vitro and in vivo. We also reviewed advantages and limitations of the described techniques. Despite limitations, immunomodulation progressively is calling by the clinic as therapy itself or as adjunct with promising results and developing potential.